Design of parallel distributed algorithm for the Permutation Flow Shop Problem - Kouki, S; Jemni, M; Ladhari, T (2010 10th Annual International Conference on New Technologies of Distributed Systems (NOTERE), 2010)
This paper deals with the resolution of the Permutation Flow Shop Problem (PFSP) which requires scheduling n jobs through m machines that are placed in series so as to minimize the makespan. In this study, we focus on parallel methods for solving the one-machine PFSP. We present a parallel distributed Algorithm for this problem with extensive computational results on cluster of computers using well-known benchmarks. The experimental evaluation of our distributed parallel algorithm gives promising results and shows clearly the benefit of the parallel paradigm to solve large-scale instances in moderate CPU time.